Unsaturated fatty acid intake during periconception and incidence of achieving pregnancy: a systematic review and meta-analysis - Gatti, Cintia Romina (2021)
Background: Previous studies suggest that maternal diets enriched in unsaturated fatty acids may have a positive effect on pregnancy success. The aim of the present study was to conduct a systematic review and meta-analysis to evaluate whether increased dietary intake of polyunsaturated fatty acids (PUFAs) or monounsaturated fatty acids (MUFAs) during the periconception period has beneficial effects on the achievement of pregnancy in women. Methods: The electronic databases PubMed, Medline and Cochrane Central Register, as well as references in related review articles, were searched to find studies assessing the effects of unsaturated fatty acid dietary intake during the periconception period on the achievement of pregnancy in women. Pregnancy was confirmed by high levels of hCG (biochemical means) and ultrasound confirmation of a gestational sac and heartbeat (clinical means). Results: For the meta-analysis evaluating the effects of periconceptional diets enriched in PUFAs on pregnancy, four articles, providing data on 2,121 patients, were included. Results showed that periconceptional intake of PUFAs has no significant effects on achieving pregnancy compared to controls, according to both the fixed effects and random effects models (RR = 0.99, 95% CI 0.98–1.00). Further secondary analysis considering ω-6 and ω-3 PUFAs separately showed no significant effects on achieving pregnancy compared to controls. On the other hand, for the meta-analysis evaluating the effects of periconceptional diets enriched in MUFAs on achieving pregnancy, five articles, providing data on 2,473 patients, were included. Results showed that periconceptional dietary intake of MUFAs has significant effects on achieving pregnancy compared to controls according to the fixed effects model (RR = 1.03, 95% CI 1.01–1.06, p < 0.02) but not to the random effects model, due to heterogeneity. A secondary meta-analysis excluding one study which led to heterogeneity showed significant effects of MUFAs on achieving pregnancy compared to controls, according to both the fixed effects and random effects models (RR = 1.03, 95% CI 1.01–1.05, p < 0.02). Conclusion: The meta-analysis of published clinical studies suggests that diets enriched in MUFAs, although not those enriched in PUFAs, may have a positive effect on pregnancy success as determined by HCG and ultrasonography.